2021
DOI: 10.1080/08870446.2021.1913157
|View full text |Cite
|
Sign up to set email alerts
|

Daily support seeking as coping strategy in dual-smoker couples attempting to quit

Abstract: Objective: Smoking cessation is a stressful event and lapses are frequent. The dynamic model of relapse has been criticized for not integrating interpersonal factors as phasic influences. Seeking social support, as a coping strategy to deal with cravings, may help to refrain from smoking. Design: Overall, 83 heterosexual dual-smoker couples reported on their craving, the extent of seeking social support from one's partner regarding smoking cessation, and their number of cigarettes smoked in smartphone-based en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Emotional support. We adapted five items from previous studies regarding emotional support, 29,38,39 and adjusted questions according to the local culture in rural China including: the frequency of children visit, the number of close relatives, the number of close friends, the frequency of seeking emotional support, and the number of emotional support providers. Participants were asked about the following questions over the past year: (i) How often does your child visit you (less than once a month, 1-3 times a month, 1-2 times a week, 3 or more times a week)?…”
Section: Variablesmentioning
confidence: 99%
“…Emotional support. We adapted five items from previous studies regarding emotional support, 29,38,39 and adjusted questions according to the local culture in rural China including: the frequency of children visit, the number of close relatives, the number of close friends, the frequency of seeking emotional support, and the number of emotional support providers. Participants were asked about the following questions over the past year: (i) How often does your child visit you (less than once a month, 1-3 times a month, 1-2 times a week, 3 or more times a week)?…”
Section: Variablesmentioning
confidence: 99%
“…Some research has shown that partner support increases and wanes depending on whether or not the smoker makes small successes in their attempt to quit smoking 8 . Interventions that enhance partner support have potential to increase cessation efforts [10][11][12] . However, these interventions have mixed effects for men and women 13 .…”
Section: Introductionmentioning
confidence: 99%